Kinetic modeling and half-life study on bioremediation of crude oil dispersed by palm bunch enhanced stimulant - Matthew N. Abonyi; Matthew C. Menkiti; Joseph T. Nwabanne; Kovo G. Akpomie (Cleaner Chemical Engineering, 2022)
The work focused on the kinetic modeling and half-life study of the bioremediation of crude oil dispersed by palm bunch enhanced stimulant. In this study, three bioremediation processes, namely; palm bunch enhanced stimulant (PES) stimulation, modified crude oil dispersant (MCD) stimulation and natural attenuated stimulation (NAS), were carried out at various petroleum hydrocarbon concentrations in polluted water media. Bacterial culture, isolations, and identification were carried out to isolate and identify the bacterial involved in the bioremediation. The process kinetics and half-life were investigated. Characterization of PES showed that PES has an appreciable quantity of potassium, phosphate, nitrate, sulphate and calcium required for cell growth and development. Bacillus pumilus, Micrococcus roseus, Micrococcus luteus, and Pseudomonas putida were the bacteria isolated from the culture. The optimum bio-stimulation efficiency of PES occurred on day 6, with BE values of 93.23%. The degradation rate constants for the PES enhanced bioremediation process decreased as the crude oil initial concentration increased from 100 to 300 mg/L. The result showed that the degradation rate constants for PES stimulated remediation were 0.11, 0.04 and 0.03 at 100, 200 and 300 mg/L of crude oil, respectively. The MCD stimulated remediation showed degradation rate constants of 0.04, 0.03 and 0.018, at crude oil concentrations of 100, 200, and 300 mg/L, respectively. The trend was the same for NAS. The longest half-life for 100 mg/L of crude oil was achieved after 79.67 days during the NAS stimulation. The results obtained from this report showed tremendous improvement to the degradation of crude oil due to the presence of PES. The degradation process was adequately described by the first order kinetic model and showed the effectiveness of PES in the remediation process. Therefore, the data obtained in this study could be applied in the design of a bioremediation system for potential application to remediation of crude oil polluted water.